Lithium ion diaphragm, preparation method thereof and preparation method of lithium ion battery
By using aerogel additives and designing oily positive electrode coatings and aqueous negative electrode coatings in lithium-ion battery separators, the problem of the adhesion between the separator and the electrode sheet is solved, the electrolyte infiltration and high temperature resistance is improved, and the battery is ensured. Consistency and stability.
Patent Information
- Application Number
- CN202411370023.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-29
AI Technical Summary
There are adhesion differences in existing lithium-ion battery separators when bonding to the electrode sheet, resulting in diaphragm folds, affecting the consistency and cycle stability of the battery.
The porous network structure of the lithium ion diaphragm is enhanced by using aerogel additives. Through the design of oily positive electrode coating slurry and aqueous negative electrode coating slurry, the wetting effect of the electrolyte and the resistance to high-temperature heat shrinkage are enhanced, and the diaphragm and electrode sheets are enhanced. Adhesion properties.
It improves the wetting effect of the electrolyte and the resistance of the high-temperature heat shrinkage of the lithium-ion separator, reduces the internal resistance of the battery, and ensures the consistency and cycle stability of the lithium battery.
Smart Images

Figure CN119419443A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of lithium battery production, and in particular to a lithium ion diaphragm and a preparation method thereof, and a preparation method of a lithium ion battery. Background Art
[0002] In order to improve the safety and electrochemical performance of lithium-ion batteries, the diaphragms usually use coating technology. For example, for PE diaphragms, common coatings include non-polar ceramic coating, water-based PVDF coating, oily PVDF coating, and oily aramid coating.
[0003] During the production process of lithium-ion battery cells, the PVDF-coated diaphragm needs to be hot-pressed with the pole piece. The pole piece and the diaphragm are bonded by PVDF, the air in the internal gap is removed, the hardness of the battery cell is increased, and the thickness consistency of the battery cell is maintained. After the battery cell is packaged by winding or stacking, the electrolyte is injected. During the hot-pressing process, the diaphragm and the pole piece are not well bonded, there will be a gap between the diaphragm and the pole piece, there will be residual gas, and the diaphragm will be wrinkled, etc., resulting in uneven distribution of internal resistance. The battery will be partially overcharged or over-discharged during the cycle, which will affect the consistency and cycle stability of the battery.
[0004] For example, the reference document CN201610853861.3 discloses a hydrophobic silica aerogel composite diaphragm for lithium-ion batteries. The diaphragm is a conventional diaphragm surface coated with a hydrophobic silica aerogel coating of different thicknesses. The silica aerogel with light weight, good heat resistance and good wettability to organic electrolyte is used as the coating material. The heat resistance, wettability and electrochemical performance of the polyolefin diaphragm are greatly improved without increasing the mass of the diaphragm. However, the composite diaphragm of this scheme fails to solve the problem of the difference in adhesion between the diaphragm and the positive electrode sheet and the negative electrode sheet, which easily causes wrinkles in the diaphragm and affects the consistency of the battery. In addition, the solvent adopts a high-boiling point solvent system, which makes it difficult to dry the diaphragm.
[0005] Another example is an aerogel lithium ion diaphragm and a preparation method thereof disclosed in the comparative document CN202210532816.3, which includes a base layer, the base layer is a non-woven fabric, at least one side of the base layer is coated with an aerogel layer, and the aerogel layer is composed of the following raw materials in parts by weight: 10-20 parts of aerogel particles, 0.3-1 parts of active agent, 2-5 parts of binder and 40-50 parts of deionized water. The thickness of the aerogel lithium ion diaphragm can reach 16 microns or even thinner, the porosity can reach more than 60%, the pore size is 0.01-0.1μm, and the surface density is 5g / m2. The aerogel battery membrane has good air permeability, high liquid absorption rate, low shrinkage rate and high strength. However, the aerogel lithium ion diaphragm of this scheme fails to solve the problem of the difference in bonding between the diaphragm and the positive electrode sheet and the negative electrode sheet, respectively, which easily causes wrinkles in the diaphragm and affects the consistency of the battery. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a lithium ion diaphragm and a preparation method thereof, as well as a preparation method of a lithium ion battery, which has good adhesion to the pole piece, improved electrolyte infiltration effect and high temperature heat shrinkage resistance.
[0007] The purpose of this disclosure is achieved through the following technical solutions:
[0008] A method for preparing a lithium ion separator comprises the following steps:
[0009] preparing an oily positive electrode coating slurry, wherein the oily positive electrode coating slurry is added with an aerogel additive, wherein the solvent of the oily positive electrode coating slurry is butanone;
[0010] preparing an aqueous negative electrode coating slurry, wherein the aqueous negative electrode coating slurry is added with an aerogel additive, wherein the solvent of the aqueous negative electrode coating slurry is ethanol;
[0011] Applying the oily positive electrode coating slurry on one side of the base film and applying the aqueous negative electrode coating slurry on the other side of the base film to obtain a transition coating separator;
[0012] The transition coating diaphragm is dried to remove butanone and ethanol, so as to obtain a lithium ion diaphragm in which an oily positive electrode coating, a base film and an aqueous negative electrode coating are sequentially arranged.
[0013] In one of the embodiments, the transition coating membrane is dried at a temperature of 30°C-60°C, and the drying time is 0.5h-3h.
[0014] In one embodiment, preparing the oily positive electrode coating slurry comprises the following steps:
[0015] The positive electrode coating binder is added to butanone, and then the positive electrode coating dispersant is added and stirred for 60 minutes to 120 minutes to obtain a positive electrode intermediate slurry;
[0016] The aerogel additive is added to the positive electrode intermediate slurry, and the mixture is stirred and dispersed for 120 min to 150 min to obtain an oily positive electrode coating slurry;
[0017] The oily positive electrode coating slurry comprises the following components by mass:
[0018] Cathode coating binder: 15%-30%;
[0019] Butanone: 44.5%-79.5%;
[0020] Positive electrode coating dispersant: 0.5%;
[0021] Aerogel additive: 5%-25%.
[0022] In one embodiment, the positive electrode coating binder is at least one of polyvinylidene fluoride PVDF and polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP; the positive electrode coating dispersant is at least one of polyethylene glycol, hexadecylbenzene sulfonic acid and modified polyacrylic acid.
[0023] In one embodiment, preparing the aqueous negative electrode coating slurry comprises the following steps:
[0024] Add the negative electrode binder and thickener into ethanol, then add the negative electrode coating dispersant, and grind and disperse for 60 minutes to 120 minutes to obtain the negative electrode intermediate slurry;
[0025] Adding aerogel additive to the negative electrode intermediate slurry, stirring and dispersing for 120min-150min, to obtain an aqueous negative electrode coating slurry;
[0026] The aqueous negative electrode coating slurry includes the following components by mass:
[0027] Negative electrode binder: 10%-20%;
[0028] Thickener: 5%-10%;
[0029] Ethanol: 45%-79.5%;
[0030] Negative electrode coating dispersant: 0.5%;
[0031] Aerogel additive: 5%-25%.
[0032] In one embodiment, the negative electrode binder is modified polyvinylidene fluoride; the negative electrode coating dispersant is at least one of polyethylene glycol, hexadecylbenzenesulfonic acid and modified polyacrylic acid.
[0033] In one embodiment, the aerogel additive includes organic aerogel and inorganic aerogel, the inorganic aerogel is at least one of SiO2 aerogel and Al2O3 aerogel; the organic aerogel is at least one of polyurea aerogel and polyimide aerogel.
[0034] In one embodiment, the thickness of the base film is 5 μm-20 μm, the thickness of the oily positive electrode coating is 1 μm-5 μm, and the thickness of the aqueous negative electrode coating is 1 μm-5 μm.
[0035] A lithium ion membrane is prepared by the lithium ion membrane preparation method as described above.
[0036] A method for preparing a lithium ion battery, comprising: preparing a lithium ion diaphragm using the method for preparing a lithium ion diaphragm;
[0037] Winding the positive electrode sheet, the lithium ion separator and the negative electrode sheet to form a winding core, and hot pressing the winding core to obtain a battery cell;
[0038] The hot-pressed battery cell is installed in a battery housing, and then liquid is injected and formed to obtain the lithium-ion battery.
[0039] Compared with the prior art, the present invention has at least the following advantages:
[0040] 1. The preparation method of the lithium ion separator mentioned above forms a large number of pores between the oily positive electrode coating and the aqueous negative electrode coating through the porous network structure of the aerogel additive, thereby improving the infiltration effect of the electrolyte. The porous network structure of the aerogel additive also improves the high temperature heat shrinkage resistance of the lithium ion separator and reduces the internal resistance of the battery;
[0041] 2. The oily positive electrode coating slurry adopts an oily solvent, and the oily positive electrode coating slurry is similar to the oily system of the positive electrode sheet coating, which improves the bonding performance between the oily positive electrode coating and the positive electrode sheet. The water-based negative electrode coating slurry adopts a water-based solvent coating, and the water-based negative electrode coating slurry is similar to the water-based system of the negative electrode sheet coating, which improves the bonding performance between the water-based negative electrode coating and the negative electrode sheet, avoiding the gap between the lithium ion diaphragm and the positive electrode sheet and the negative electrode sheet, which causes the lithium ion diaphragm to wrinkle, so that the consistency and cycle stability of the prepared lithium battery are better;
[0042] 3. The oily positive electrode coating slurry uses the solvent butanone, and the aqueous negative electrode coating slurry uses the solvent ethanol. Both butanone and ethanol are low-boiling point solvents, which make the oily positive electrode coating slurry and the aqueous negative electrode coating slurry easily volatilize during the baking process, avoiding solvent residue in the lithium ion diaphragm. The boiling points of butanone and ethanol are close, which makes the drying time of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry similar, thereby making the formed lithium ion diaphragm more uniform, so that the battery made of the lithium ion diaphragm has better consistency. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present disclosure, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present disclosure and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0044] Figure 1 A step diagram of a method for preparing a lithium ion separator according to an embodiment. DETAILED DESCRIPTION
[0045] In order to facilitate the understanding of the present disclosure, the present disclosure will be described more fully below with reference to the relevant drawings. The preferred embodiments of the present disclosure are given in the drawings. However, the present disclosure can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present disclosure more thoroughly and comprehensively understood.
[0046] It should be noted that when an element is referred to as being "fixed to" another element, it may be directly on the other element or there may be a central element. When an element is considered to be "connected to" another element, it may be directly connected to the other element or there may be a central element at the same time. The terms "vertical", "horizontal", "left", "right" and similar expressions used herein are for illustrative purposes only and do not represent the only implementation method.
[0047] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present disclosure. The terms used herein in the specification of the present disclosure are only for the purpose of describing specific embodiments and are not intended to limit the present disclosure. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0048] In order to better understand the technical solutions and beneficial effects of the present invention, the present invention is further described in detail below in conjunction with specific embodiments:
[0049] The present invention relates to a method for preparing a lithium ion diaphragm. In one embodiment, the method comprises the following steps: preparing an oily positive electrode coating slurry, wherein the oily positive electrode coating slurry is added with an aerogel additive, wherein the solvent of the oily positive electrode coating slurry is butanone; preparing an aqueous negative electrode coating slurry, wherein the aqueous negative electrode coating slurry is added with an aerogel additive, wherein the solvent of the aqueous negative electrode coating slurry is ethanol; applying the oily positive electrode coating slurry to one side of a base film and the other side of the aqueous negative electrode coating slurry to obtain a transition coating diaphragm; drying the transition coating diaphragm to remove butanone and ethanol, thereby obtaining a lithium ion diaphragm in which the oily positive electrode coating, the base film and the aqueous negative electrode coating are sequentially arranged.
[0050] See also Figure 1 , which is a method for preparing a lithium ion separator according to an embodiment of the present invention, comprising the following steps:
[0051] S101 prepares an oily positive electrode coating slurry, to which an aerogel additive is added, wherein the solvent of the oily positive electrode coating slurry is butanone; in this embodiment, the aerogel additive can increase the high-temperature thermal shrinkage resistance of the diaphragm and improve the absorbency of the electrolyte in the oily positive electrode coating.
[0052] S103 prepares an aqueous negative electrode coating slurry, wherein the aqueous negative electrode coating slurry is added with inorganic aerogel and organic aerogel, wherein the solvent of the aqueous negative electrode coating slurry is ethanol. In this embodiment, the aerogel additive can increase the high temperature heat shrinkage resistance of the separator and improve the absorbency of the electrolyte in the aqueous negative electrode coating.
[0053] S105: coating the oily positive electrode coating slurry on one side of the base film and coating the aqueous negative electrode coating slurry on the other side to obtain a transition coating diaphragm; in the present embodiment, the oily positive electrode coating slurry is located on the side opposite to the positive electrode sheet, and the aqueous negative electrode coating slurry is located on the side opposite to the negative electrode sheet, so that the oily positive electrode coating of the lithium ion diaphragm is bonded to the positive electrode sheet, and the aqueous negative electrode coating is bonded to the negative electrode sheet.
[0054] S107 dries the transition coating diaphragm to remove butanone and ethanol, so as to obtain a lithium ion diaphragm in which an oily positive electrode coating, a base film and an aqueous negative electrode coating are sequentially arranged. In this embodiment, during the drying of the diaphragm, the solvent with a lower boiling point evaporates first, and the slurry with a higher boiling point evaporates more slowly. When the slurry on one side of the base film is dried, the slurry on the other side of the base film is not completely dried, resulting in different degrees of dryness and wetness of the lithium ion diaphragm, so that the lithium ion diaphragm has residual solvent. The boiling point of butanone is 79°C, and the boiling point of ethanol is 78°C. Both butanone and ethanol are low-boiling-point solvents, which makes it easy for the solvents of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry to evaporate cleanly, and the boiling point difference between the butanone solvent of the oily positive electrode coating slurry and the ethanol solvent of the aqueous negative electrode coating slurry is less than 10°C, which makes the low-temperature drying speed of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry similar, so that the drying time of the oily positive electrode coating and the aqueous positive electrode coating is the same, and the formed lithium ion separator is more uniform.
[0055] The above-mentioned preparation method of the lithium ion diaphragm, through the porous network structure of the aerogel additive, forms a large number of pores between the oily positive electrode coating and the water-based negative electrode coating, thereby improving the infiltration effect of the electrolyte, and the porous network structure of the aerogel additive also improves the high-temperature heat shrinkage resistance of the lithium ion diaphragm and reduces the internal resistance of the battery; the oily positive electrode coating slurry adopts an oily solvent, and the oily positive electrode coating slurry is similar to the oily system of the positive electrode sheet coating, which improves the bonding performance of the oily positive electrode coating and the positive electrode sheet; the water-based negative electrode coating slurry adopts a water-based solvent coating, and the water-based negative electrode coating slurry is similar to the water-based system of the negative electrode sheet coating, which improves the water-based negative electrode coating and the negative electrode sheet The adhesive property avoids the gap between the lithium ion diaphragm and the positive electrode sheet and the negative electrode sheet, which causes the lithium ion diaphragm to wrinkle, so that the consistency and cycle stability of the lithium battery are better; the oily positive electrode coating slurry adopts the solvent butanone, and the aqueous negative electrode coating slurry adopts the solvent ethanol. Both butanone and ethanol are low-boiling point solvents, which makes the oily positive electrode coating slurry and the aqueous negative electrode coating slurry easy to volatilize during the baking process, avoiding the solvent from remaining in the lithium ion diaphragm. The boiling points of butanone and ethanol are close, which makes the drying time of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry similar, thereby making the formed lithium ion diaphragm more uniform, so that the consistency of the battery made of the lithium ion diaphragm is better.
[0056] In one of the embodiments, the transition coating diaphragm is dried at a temperature of 30°C-60°C, and the drying time is 0.5h-3h. In this embodiment, when the drying temperature of the transition diaphragm is too high, the solvent volatilization rate of the oily positive electrode coating slurry and the water-based negative electrode coating slurry is relatively fast. When the solvent volatilizes too fast, it is easy to cause the coating surface to be uneven, so that the obtained lithium ion diaphragm is unevenly stressed, which causes wrinkles when the lithium ion diaphragm and the pole piece are wound. Butanone and ethanol are both low-boiling point solvents. Butanone and ethanol are easy to volatilize during the baking process at a low baking temperature. The original diaphragm drying process requires more than 8 hours. The drying time of the transition coating diaphragm is reduced to 0.5h-3h, which reduces the drying time of the transition coating diaphragm and improves the production speed of the lithium ion diaphragm.
[0057] Furthermore, a double-sided coating device is used to coat both sides of the base film at the same time. The double-sided coating device includes two die heads respectively arranged on both sides of the base film. The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on both sides of the base film through the two die heads to obtain a transition coating diaphragm. The transition coating diaphragm is then dried by a floating drying box to dry the oily positive electrode coating slurry and the aqueous negative electrode coating slurry on both sides of the base film, so that an oily positive electrode coating and an aqueous negative electrode coating are respectively formed on both sides of the transition coating diaphragm, thereby making the uniformity of the dried oily positive electrode coating and the aqueous negative electrode coating better and accelerating the production efficiency of the lithium ion diaphragm.
[0058] In one embodiment, the base film is a composite coating of PE and PP. In this embodiment, the composite coating of PE and PP is more resistant to high temperatures than PP; the melting point and closed-cell temperature of PP are higher than those of PE, and the composite coating of PE and PP makes the base film have the advantages of low closed-cell temperature and high melting temperature, and also has the characteristics of high anti-oxidation and anti-puncture strength.
[0059] In one embodiment, preparing the oily positive electrode coating slurry comprises the following steps:
[0060] The positive electrode coating binder is added to butanone, and then the positive electrode coating dispersant is added and stirred for 60 minutes to 120 minutes to obtain a positive electrode intermediate slurry;
[0061] The aerogel additive is added to the positive electrode intermediate slurry, and the mixture is stirred and dispersed for 120 min to 150 min to obtain an oily positive electrode coating slurry;
[0062] The oily positive electrode coating slurry comprises the following components by mass:
[0063] Cathode coating binder: 15%-30%;
[0064] Butanone: 44.5%-79.5%;
[0065] Positive electrode coating dispersant: 0.5%;
[0066] Aerogel additive: 5%-25%.
[0067] In this embodiment, the positive electrode coating binder is added with butanone and mixed evenly, and after adding 5%-25% of the aerogel additive, the aerogel additive is evenly distributed in the prepared oily positive electrode coating slurry. When the content of aerogel is less than 5%, the porosity of the aerogel additive is low, and the liquid absorption effect on the electrolyte decreases. When the content of aerogel additive is greater than 25%, the porosity of the aerogel additive is high, but the aerogel additive will affect the bonding performance of the oily positive electrode coating. The porous network structure of the aerogel additive makes the aerogel additive have a high porosity. The aerogel additive is distributed in the oily positive electrode coating formed after the oily positive electrode coating slurry is dried, and there are a large number of pores, so that the oily positive electrode coating can accommodate more electrolyte. The porous network structure of the aerogel additive also improves the wettability of the electrolyte and the oily positive electrode coating. The thermal conductivity of the aerogel additive is low, so that the high temperature heat shrinkage resistance of the oily positive electrode coating formed after the oily positive electrode coating slurry is dried is improved.
[0068] In one of the embodiments, the positive electrode coating binder is at least one of polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP; the positive electrode coating dispersant is at least one of polyethylene glycol, hexadecylbenzene sulfonic acid and modified polyacrylic acid. In this embodiment, when the mixing speed of polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP adding butanone is slow, butanone is preheated. The oily positive electrode coating formed by polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP is similar to the oily system of the positive electrode material of the positive electrode sheet, so that the bonding performance of polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP connected to the positive electrode sheet is stronger. When polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP is hot-pressed, polyvinylidene fluoride PVDF or polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP can fully bond the inorganic aerogel and the organic aerogel together and be tightly connected with the lithium ion separator.
[0069] In one embodiment, preparing the aqueous negative electrode coating slurry comprises the following steps:
[0070] Add the negative electrode binder and thickener into ethanol, then add the negative electrode coating dispersant, and grind and disperse for 60 minutes to 120 minutes to obtain the negative electrode intermediate slurry;
[0071] Adding aerogel additive to the negative electrode intermediate slurry, stirring and dispersing for 120min-150min, to obtain an aqueous negative electrode coating slurry;
[0072] The aqueous negative electrode coating slurry includes the following components by mass:
[0073] Negative electrode binder: 10%-20%;
[0074] Thickener: 5%-10%;
[0075] Ethanol: 45%-79.5%;
[0076] Negative electrode coating dispersant: 0.5%;
[0077] Aerogel additive: 5%-25%.
[0078] In this embodiment, when the content of aerogel is less than 5%, the porosity of the aerogel additive is low, and the liquid absorption effect on the electrolyte decreases. When the content of aerogel additive is greater than 25%, the porosity of the aerogel additive is high, but the aerogel additive affects the bonding performance of the aqueous negative electrode coating. The bonding performance of the aqueous negative electrode coating is relatively small, and the aerogel additive has a greater impact on the bonding performance of the aqueous negative electrode coating. 5%-25% aerogel additive is added to the negative electrode intermediate slurry. The porous network structure of the aerogel additive makes the aerogel additive have a high porosity, so that the aqueous negative electrode coating formed after the aqueous negative electrode coating slurry is dried has a large number of pores, so that the aqueous negative electrode coating can accommodate more electrolyte. The porous network structure of the aerogel additive also improves the wettability of the electrolyte and the aqueous negative electrode coating. The thermal conductivity of the aerogel additive is low, so that the high-temperature heat shrinkage resistance of the aqueous negative electrode coating formed after the aqueous negative electrode coating slurry is dried is improved. The aqueous negative electrode coating formed by the aqueous negative electrode coating slurry and the negative electrode material of the negative electrode sheet both adopt an aqueous system, which improves the adhesion between the aqueous negative electrode coating and the negative electrode sheet. Since the negative electrode intermediate slurry is an aqueous system, the negative electrode binder needs to be evenly dispersed in the aqueous solvent ethanol to form a stable suspension or emulsion state of the aqueous negative electrode coating slurry, and the negative electrode binder needs to be fully ground and dispersed by grinding equipment. The negative electrode intermediate slurry is continuously ground by grinding equipment so that the negative electrode binder in the negative electrode intermediate slurry is evenly dispersed. Ethyl cellulose can adjust the viscosity of the negative electrode coating slurry so that the prepared aqueous negative electrode coating slurry is easy to apply, thereby making the obtained aqueous negative electrode coating slurry more stable.
[0079] Furthermore, the thickener is one or more of ethyl cellulose or modified cellulose. Modified cellulose such as highly substituted hydroxypropyl cellulose, ethyl cellulose and highly substituted hydroxypropyl cellulose are soluble in ethanol, so that the viscosity of the aqueous negative electrode coating slurry is increased, thereby controlling the viscosity of the aqueous negative electrode coating slurry, so that the aqueous negative electrode coating slurry is easily coated on the surface of the base film.
[0080] In one embodiment, the negative electrode binder is modified polyvinylidene fluoride, and the negative electrode coating dispersant is one or two of polyethylene glycol, hexadecylbenzene sulfonic acid and modified polyacrylic acid. In this embodiment, polyvinylidene fluoride is modified to increase hydrophilic groups, so that hydrophilic groups are introduced into the modified polyvinylidene fluoride, and the hydrophilic groups are polar, so that the modified polyvinylidene fluoride is soluble in polar ethanol. In this embodiment, the negative electrode coating dispersant is soluble in ethanol solvent, and the negative electrode coating dispersant can increase the surface activity of particles or powders, which can effectively prevent them from precipitating or aggregating in liquids, and improve the wettability between aerogels, so that the negative electrode binder and aerogel additives are evenly dispersed in ethanol, thereby forming a stable aqueous negative electrode coating slurry in a suspension or emulsion state.
[0081] Further, in one embodiment, the solid content of the oily positive electrode coating slurry is 10%-45%, and the solid content of the aqueous negative electrode coating slurry is 15%-45%. In this embodiment, when the solid content of the oily positive electrode coating slurry is less than 15%, the content of polyvinylidene fluoride is too low, so that the coating is thin, the adhesion performance between polyvinylidene fluoride and the positive and negative electrode sheets is insufficient, and the problem of falling off is easy to occur. When the solid content of the oily positive electrode coating slurry is greater than 45%, the thickness of the oily positive electrode coating slurry is thicker, thereby increasing the thickness between the positive electrode sheet, the separator and the negative electrode sheet, thereby reducing the energy density of the battery. When the solid content of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry is between 15%-45%, the oily positive electrode coating slurry and the aqueous negative electrode coating slurry contain sufficient polyvinylidene fluoride, so that the oily positive electrode coating and the aqueous negative electrode coating effectively bond the positive electrode sheet, the base film and the negative electrode sheet together.
[0082] Furthermore, in this embodiment, when the amount of aerogel additive added to the oily positive electrode coating slurry and the amount of aerogel additive added to the aqueous negative electrode coating slurry are different, the porosity in the oily positive electrode coating and the aqueous negative electrode coating will also be different. Therefore, the proportion of aerogel additive added to the oily positive electrode coating slurry is the same as the proportion of aerogel additive added to the aqueous negative electrode coating, so that the porosity in the oily positive electrode coating and the aqueous negative electrode coating is the same, and when the oily positive electrode coating and the aqueous negative electrode coating are infiltrated with electrolyte, the electrolyte capacity infiltrated on the positive and negative electrode sheets is the same.
[0083] Furthermore, when the proportion of aerogel additive added to the oily positive electrode coating slurry is the same as the proportion of aerogel additive added to the aqueous negative electrode coating, the positive electrode coating binder of the oily positive electrode coating slurry and the thickener and negative electrode coating binder of the aqueous negative electrode coating slurry make the solid content of the oily positive electrode coating slurry different from the solid content of the aqueous negative electrode coating slurry, resulting in a deviation in the aerogel additives of the oily positive electrode coating and the aqueous negative electrode coating formed after the oily positive electrode coating slurry and the aqueous negative electrode coating slurry are dried. Therefore, after adding the aerogel additive to the negative electrode intermediate slurry and stirring and dispersing for 120min-150min to obtain the aqueous negative electrode coating slurry, the solid content of the aqueous negative electrode coating slurry is adjusted, including the following steps:
[0084] The oily positive electrode coating slurry is sampled and baked to obtain the solid content of the oily positive electrode coating slurry, and the water-based negative electrode coating slurry is sampled and baked to obtain the solid content of the water-based negative electrode coating slurry;
[0085] When the solid content of the oily positive electrode coating slurry is greater than 0.5% of the solid content of the aqueous negative electrode coating slurry, the aqueous negative electrode coating slurry is adjusted by adding 1% of modified polyvinylidene fluoride powder and mixing to increase the solid content of the prepared aqueous negative electrode coating slurry.
[0086] When the solid content of the oily positive electrode coating slurry is greater than 0.5% of the solid content of the aqueous negative electrode coating slurry, the aqueous negative electrode coating slurry is adjusted by adding 2% ethanol and mixing to reduce the solid content of the prepared aqueous negative electrode coating slurry.
[0087] In this embodiment, by adjusting the solid content of the aqueous negative electrode coating slurry, the difference in thickness between the oily positive electrode coating formed after the oily positive electrode coating slurry is dried and the aqueous negative electrode coating formed after the aqueous negative electrode coating slurry is dried is reduced, thereby reducing the deviation in the distribution of the aerogel additive in the oily positive electrode coating and the aqueous negative electrode coating, thereby maintaining consistency in the electrolyte content infiltrated on both sides of the lithium ion separator.
[0088] In one embodiment, the aerogel additive includes organic aerogel and inorganic aerogel, wherein the inorganic aerogel is at least one of SiO2 aerogel and Al2O3 aerogel; and the organic aerogel is at least one of polyurea aerogel and polyimide aerogel. In this embodiment, SiO2 aerogel and Al2O3 aerogel have the characteristics of high temperature resistance, so that in the subsequent PVDF pressing process, they have strong heat resistance and prevent breakage during the hot pressing process, so that the SiO2 aerogel and Al2O3 aerogel in the formed oily positive electrode coating slurry and water-based negative electrode coating slurry are not easily damaged, and the heat resistance of the oily positive electrode coating and the water-based negative electrode coating is improved. Polyurea aerogel and polyimide aerogel have the characteristics of high mechanical properties, good thermal stability, and extremely low thermal conductivity. Polyurea aerogel and polyimide aerogel can improve the thermal shrinkage resistance. When the prepared lithium ion membrane is hot-pressed with the positive electrode sheet and the negative electrode sheet, due to the good heat resistance of SiO2 aerogel, Al2O3 aerogel, polyurea aerogel and polyimide aerogel, their structure is not easy to break, so that the prepared lithium ion membrane has good electrolyte absorption capacity and thermal shrinkage resistance.
[0089] Furthermore, the inorganic aerogel also includes at least one of carbon nanotube aerogel and graphene aerogel. Carbon nanotube aerogel and graphene aerogel have good conductivity and can form a conductive network on the surface of the diaphragm to promote the transmission of electrons, thereby reducing the interfacial reaction resistance of the battery; the organic aerogel also includes at least one of polyurethane aerogel, polybenzoxazine aerogel, syndiotactic polystyrene aerogel, poly-meta-phenylenediamine aerogel, polyamide aerogel, polyvinylidene fluoride aerogel, and polypyrrole aerogel. This type of organic aerogel improves the absorption performance of the electrolyte of the lithium ion diaphragm.
[0090] Furthermore, in one of the embodiments, when the added organic aerogel is hydrophobic, such as the hydrophobicity of the polyurea aerogel is strong, the dispersion and wetting effect of the polyurea aerogel in the aqueous negative electrode coating slurry is not good. Before adding the aerogel additive and stirring and dispersing for 120min-150min, the added negative electrode coating dispersant is stirred for 60min-120min, and the wetting agent hexadecylbenzenesulfonic acid is also added. In this embodiment, hexadecylbenzenesulfonic acid reduces the surface tension of the polyurea aerogel, so that the solvent ethanol can wet the polyurea aerogel, avoiding the uneven distribution of the polyurea aerogel, resulting in uneven pore distribution of the obtained lithium ion diaphragm aqueous positive electrode coating, so that the polyurea aerogel is dispersed in the aqueous positive electrode coating slurry, so that the aqueous positive electrode coating has good electrolyte infiltration and high temperature heat shrinkage resistance.
[0091] In one embodiment, the mass component of the organic aerogel in the aerogel additive is 20%-80%, and the mass component of the inorganic aerogel in the aerogel additive is 20%-80%. In this embodiment, the organic aerogel has a good ability to absorb electrolyte and a high mechanical strength, and the inorganic aerogel has good heat resistance and shrinkage resistance. The inorganic aerogel has good heat resistance in the aerogel additive. When the inorganic aerogel accounts for a large proportion in the aerogel additive, the lithium ion diaphragm has better heat resistance during hot pressing with the positive electrode sheet and the negative electrode sheet, thereby reducing the damage of the organic aerogel and the inorganic aerogel.
[0092] In one embodiment, the thickness of the base film is 5μm-20μm, the thickness of the oily positive electrode coating slurry is 1μm-5μm, and the thickness of the aqueous negative electrode coating slurry is 1μm-5μm. In this embodiment, the oily positive electrode coating slurry and the aqueous negative electrode coating slurry of the same thickness can be coated on both sides of the base film, respectively. The base film can provide good support strength and insulation performance. The oily positive electrode coating slurry can form a coating with a thickness of 1μm-5μm after drying, so that the oily positive electrode coating can accommodate a certain amount of electrolyte. The aqueous negative electrode coating slurry can form a coating with a thickness of 1μm-5μm after drying, so that the aqueous negative electrode coating can accommodate a certain amount of electrolyte, and the high temperature heat shrinkage resistance of the lithium ion separator is improved.
[0093] Furthermore, when the coating thickness of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry are different, the bonding state between the lithium ion separator and the positive electrode sheet and the negative electrode sheet is different. The coating thickness of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry is controlled to control the thickness of the oily positive electrode coating and the thickness of the aqueous negative electrode coating after drying. It can be understood that the slurry of the oily positive electrode coating and the slurry of the aqueous negative electrode coating are coated separately by controlling the surface density of the coating of the two dies through a double-sided coating device. The coating openings of the two dies are the same size, and the viscosity of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry is controlled to be the same. The coating of the two dies can be controlled to coat the oily positive electrode coating slurry and the aqueous negative electrode coating slurry of similar thickness on both sides of the base film. Therefore, after preparing the aqueous negative electrode coating slurry, the viscosity of the aqueous negative electrode coating slurry is also adjusted, including the following steps:
[0094] Testing and comparing the viscosity of the aqueous negative electrode coating slurry and the viscosity of the oily positive electrode coating slurry;
[0095] If the viscosity of the aqueous negative electrode coating slurry is less than the viscosity of the oily positive electrode coating slurry, the viscosity of the aqueous negative electrode coating slurry is increased, 0.1% ethyl cellulose accounting for the total mass of the aqueous negative electrode coating slurry is added to the aqueous negative electrode coating slurry for stirring and dispersion, and then the adjusted viscosity of the aqueous negative electrode coating slurry is tested, and the viscosity of the aqueous negative electrode coating slurry and the viscosity of the oily positive electrode coating slurry are repeatedly tested and compared;
[0096] If the viscosity of the aqueous negative electrode coating slurry is less than that of the oily positive electrode coating slurry, 0.1% polyacrylate accounting for the total mass of the oily positive electrode coating slurry is added to the oily positive electrode coating slurry for stirring and dispersion, and then the viscosity of the adjusted oily positive electrode coating slurry is tested, and the viscosity of the aqueous negative electrode coating slurry and the viscosity of the oily positive electrode coating slurry are repeatedly tested and compared.
[0097] In this embodiment, by controlling the viscosity of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry to be the same, the two die heads are used to coat the oily positive electrode coating slurry and the aqueous negative electrode coating slurry of similar thickness on both sides of the base film respectively, and the coating thickness of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry are similar, so that the thickness of the oily positive electrode coating formed after drying is similar to the thickness of the aqueous negative electrode coating, the porosity of the oily positive electrode coating and the aqueous negative electrode coating slurry on both sides of the lithium ion separator is similar, and the bonding state of the lithium ion separator and the positive electrode sheet and the negative electrode sheet is similar, so that the uniformity between the positive electrode sheet, the lithium ion separator and the negative electrode sheet is better, and wrinkles on the lithium ion separator are avoided.
[0098] In one of the embodiments, when preparing the oily positive electrode coating slurry or the aqueous negative electrode coating slurry, 1%-5% of the total amount of the coating slurry can also be added as a pore-forming agent ammonium bicarbonate. In this embodiment, the ammonium bicarbonate decomposes during the baking process of the oily positive electrode coating slurry or the aqueous negative electrode coating slurry, so that the oily positive electrode coating slurry or the aqueous negative electrode coating slurry forms a pore structure to increase the specific surface area, thereby reducing the resistance, and also improving the diffusion of the electrolyte, so that the electrolyte infiltrates the oily positive electrode coating or the aqueous negative electrode faster.
[0099] The application also provides a lithium ion separator prepared by the lithium ion separator preparation method as described above. In this embodiment, the oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on both sides of the base film and dried to form a lithium ion separator in which the oily positive electrode coating, the base film and the aqueous negative electrode coating are sequentially stacked.
[0100] The present application also provides a method for preparing a lithium ion battery, characterized in that it comprises a lithium ion diaphragm obtained by the method for preparing a lithium ion diaphragm described in any of the above embodiments,
[0101] Winding the positive electrode sheet, the lithium ion separator and the negative electrode sheet to form a winding core, and hot pressing the winding core to obtain a battery cell;
[0102] The hot-pressed battery cell is installed in a battery housing, and then liquid is injected and formed to obtain the lithium-ion battery.
[0103] In this embodiment, the polyvinylidene fluoride PDVF in the oily positive electrode coating of the lithium ion separator is heated and contacts the positive electrode sheet, so that the positive electrode sheet and the oily positive electrode coating are fully bonded together. The polyvinylidene fluoride PDVF in the aqueous negative electrode coating of the lithium ion separator is heated and contacts the negative electrode sheet, so that the negative electrode sheet and the aqueous positive electrode coating are fully bonded together, and the negative electrode sheet and the aqueous negative electrode coating are fully bonded together.
[0104] In one embodiment, the pressure of the hot pressing process is 0.05Mpa~1Mpa, and the holding time of the hot pressing process is 3h~6h. In this embodiment, when the pressure on the organic aerogel and the inorganic aerogel is too large, they are easily broken, thereby destroying the effect of the organic aerogel and the inorganic aerogel in the oily positive electrode coating and the water-based negative electrode coating. The hot pressing pressure is 0.05Mpa~1Mpa, so that the pressure between the positive electrode sheet and the lithium ion diaphragm and the negative electrode sheet is relatively small, preventing the aerogel additive from being damaged by pressure and losing its effect. By holding the pressure for 3h~6h, the positive electrode sheet, the lithium ion diaphragm and the negative electrode sheet are tightly bonded, thereby reducing the gap between the lithium ion diaphragm and the positive electrode sheet and the negative electrode sheet, and avoiding the problem of wrinkles in the lithium ion diaphragm.
[0105] Furthermore, the temperature of the hot pressing process is 45°C to 85°C. Therefore, when the core is hot pressed, the temperature needs to be controlled at 85°C. When the hot pressing process temperature is less than 45°C, the polyvinylidene fluoride PDVF is not melted well, the oily positive electrode coating has poor adhesion to the positive electrode sheet, and the water-based negative electrode coating has poor adhesion to the negative electrode sheet, so that air is retained between the lithium ion diaphragm and the positive electrode sheet and the negative electrode sheet, causing the lithium ion diaphragm to be easily wrinkled, thereby affecting the performance of the lithium ion battery. When the hot pressing process temperature is greater than 85°C, the polyvinylidene fluoride PDVF has a better melting effect, but when the organic aerogel and inorganic aerogel are pressurized and heated at a high temperature, the organic aerogel and inorganic aerogel will not melt well. The porous structure of the organic aerogel is easily destroyed, so that the organic aerogel and inorganic aerogel of the oily positive electrode coating and the water-based negative electrode coating are destroyed, and the lithium ion membrane reduces the infiltration of the electrolyte and the resistance to high-temperature thermal shrinkage; when the temperature of the hot pressing process is 45-85°C, the melting effect of polyvinylidene fluoride PDVF is better, so that the adhesion between the oily positive electrode coating and the positive electrode sheet is better, and the adhesion between the water-based negative electrode coating and the negative electrode sheet is better. The porous structure of the organic aerogel and the inorganic aerogel in the lithium ion membrane is intact, so that the lithium ion membrane improves the infiltration effect of the electrolyte and the resistance to high-temperature thermal shrinkage.
[0106] Compared with the prior art, the present invention has at least the following advantages:
[0107] 1. The preparation method of the lithium ion separator mentioned above forms a large number of pores between the oily positive electrode coating and the aqueous negative electrode coating through the porous network structure of the aerogel additive, thereby improving the infiltration effect of the electrolyte. The porous network structure of the aerogel additive also improves the high temperature heat shrinkage resistance of the lithium ion separator and reduces the internal resistance of the battery;
[0108] 2. The oily positive electrode coating slurry adopts an oily solvent, and the oily positive electrode coating slurry is similar to the oily system of the positive electrode sheet coating, which improves the bonding performance between the oily positive electrode coating and the positive electrode sheet. The water-based negative electrode coating slurry adopts a water-based solvent coating, and the water-based negative electrode coating slurry is similar to the water-based system of the negative electrode sheet coating, which improves the bonding performance between the water-based negative electrode coating and the negative electrode sheet, avoiding the gap between the lithium ion diaphragm and the positive electrode sheet and the negative electrode sheet, which causes the lithium ion diaphragm to wrinkle, so that the consistency and cycle stability of the prepared lithium battery are better;
[0109] 3. The oily positive electrode coating slurry uses the solvent butanone, and the aqueous negative electrode coating slurry uses the solvent ethanol. Both butanone and ethanol are low-boiling point solvents, which make the oily positive electrode coating slurry and the aqueous negative electrode coating slurry easily volatilize during the baking process, avoiding solvent residue in the lithium ion diaphragm. The boiling points of butanone and ethanol are close, which makes the drying time of the oily positive electrode coating slurry and the aqueous negative electrode coating slurry similar, thereby making the formed lithium ion diaphragm more uniform, so that the battery made of the lithium ion diaphragm has better consistency.
[0110] Some specific examples are listed below, and if % is mentioned, it means percentage by weight. It should be noted that the following examples do not exhaust all possible situations, and the materials used in the following examples can be obtained from commercial sources unless otherwise specified.
[0111] Example 1
[0112] First, 0.5% dispersant and 5% ethyl cellulose thickener were added to ethanol and stirred evenly, and then 10% modified PVDF powder was slowly added, and the kneading machine speed was set to 1000 rpm, and then the slurry was ground and dispersed for 60 minutes by a kneading process to make the slurry mixed evenly; 10% silica aerogel and 10% polyurea aerogel were added thereto, and stirred to make them mixed evenly, the stirring time was 120 minutes, and the speed was 1500 rpm to obtain an aqueous negative electrode coating slurry;
[0113] Then, 0.5% of dispersant, 5% of polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% of polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was mixed evenly by a kneading process for 60 minutes to obtain an oily positive electrode coating slurry;
[0114] The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on a base film with a thickness of 5-20 μm and a porosity of 20-70%, and the coating speed is 25 m / min to obtain a transition coating diaphragm with a thickness of 3 μm of the oily positive electrode coating slurry coating and a thickness of 3 μm of the aqueous negative electrode coating slurry coating; then the transition coating diaphragm is dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Example 1.
[0115] Example 2
[0116] First, 0.5% dispersant and 5% ethyl cellulose thickener were added to ethanol and stirred evenly, and then 10% modified PVDF powder was slowly added, the kneading machine speed was set to 1000 rpm, and then the slurry was ground and dispersed for 60 minutes through a kneading process to mix the slurry evenly to obtain an aqueous negative electrode coating slurry.
[0117] Then, 0.5% dispersant, 5% polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was treated by kneading process for 60 minutes to mix evenly, 10% silica aerogel and 10% polyurea aerogel were added thereto, and stirred to mix evenly, the stirring time was 120 minutes, and the speed was 1500 rpm to obtain an oily positive electrode coating slurry.
[0118] The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on a base film with a thickness of 5-20 μm and a porosity of 20-70%, and the coating speed is 25 m / min to obtain a transition coating diaphragm with a thickness of 3 μm of the oily positive electrode coating slurry coating and a thickness of 3 μm of the aqueous negative electrode coating slurry coating; then the transition coating diaphragm is dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Example 2.
[0119] Example 3
[0120] First, add 0.5% dispersant and 5% ethyl cellulose thickener to ethanol and stir evenly, then slowly add 10% modified PVDF powder, set the kneading machine speed to 1000rpm, and then grind and disperse the slurry through a kneading process for 60min to make the slurry mix evenly, add 10% silica aerogel and 10% polyurea aerogel thereto, stir to make it mix evenly, the stirring time is 120min, and the speed is 1500rpm to obtain an aqueous negative electrode coating slurry.
[0121] Then, 0.5% dispersant, 5% polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was treated by kneading process for 60 minutes to mix evenly, 10% silica aerogel and 10% polyurea aerogel were added thereto, and stirred to mix evenly, the stirring time was 120 minutes, and the speed was 1500 rpm to obtain an oily positive electrode coating slurry.
[0122] The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on a base film with a thickness of 5-20 μm and a porosity of 20-70%, and the coating speed is 25 m / min to obtain a transition coating diaphragm with a thickness of 3 μm of the oily positive electrode coating slurry coating and a thickness of 3 μm of the aqueous negative electrode coating slurry coating; then the transition coating diaphragm is dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Example 3.
[0123] Example 4
[0124] First, add 0.5% dispersant and 5% ethyl cellulose thickener to ethanol, stir evenly, then slowly add 10% modified PVDF powder, set the kneading machine speed to 1000rpm, and then grind and disperse for 60min through kneading process to make the slurry mixed evenly. Add 10% silica aerogel and 10% poly(m-phenylenediamine) aerogel thereto, stir to make them mixed evenly, the stirring time is 120min, the speed is 1500rpm, and the aqueous negative electrode coating slurry is obtained. Add 5% ammonium bicarbonate to the aqueous negative electrode coating slurry and stir at 1000rpm for 60min.
[0125] Then, 0.5% dispersant, 5% polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was treated by kneading process for 60 minutes to mix evenly, 10% silica aerogel and 10% polyurea aerogel were added thereto, and the mixture was stirred to mix evenly, the stirring time was 120 minutes, and the speed was 1500 rpm to obtain an oily positive electrode coating slurry.
[0126] The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on a base film with a thickness of 5-20 μm and a porosity of 20-70%, and the coating speed is 25 m / min to obtain a transition coating diaphragm with a thickness of 3 μm of the oily positive electrode coating slurry coating and a thickness of 3 μm of the aqueous negative electrode coating slurry coating; then the transition coating diaphragm is dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Example 4.
[0127] Comparative Example 1
[0128] First, add 0.5% dispersant and 5% ethyl cellulose thickener to ethanol and stir evenly, then slowly add 10% modified PVDF powder, set the kneading machine speed to 1000rpm, and then grind and disperse the slurry through a kneading process for 60min to make the slurry mix evenly, add 20% silica aerogel thereto, stir to make it mix evenly, the stirring time is 120min, and the speed is 1500rpm to obtain an aqueous negative electrode coating slurry.
[0129] Then, 0.5% dispersant, 5% polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was treated by kneading process for 60 minutes to mix evenly, 20% silica aerogel was added thereto, and stirred to mix evenly, the stirring time was 120 minutes, and the speed was 1500 rpm to obtain an oily positive electrode coating slurry.
[0130] The oily positive electrode coating slurry and the aqueous negative electrode coating slurry are respectively coated on a base film with a thickness of 5-20 μm and a porosity of 20-70%, and the coating speed is 50 m / min to obtain a transition coating diaphragm with a thickness of 3 μm of the oily positive electrode coating slurry coating and a thickness of 3 μm of the aqueous negative electrode coating slurry coating; and then the transition coating diaphragm is dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Example 1, cell.
[0131] Comparative Example 2
[0132] First, 0.5% dispersant, 5% polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP and 10% polyvinylidene fluoride PVDF powder were added to butanone, the kneading machine speed was set to 1000 rpm, and then the slurry was mixed evenly by kneading process for 60 minutes, 10% silica aerogel and 10% polyurea aerogel were added thereto, and the mixture was stirred to make it evenly mixed. The stirring time was 120 minutes and the speed was 1500 rpm to obtain the positive electrode oily coating slurry.
[0133] The coating slurry is applied on a base film with a thickness of 5-20 μm and a porosity of 20-70% at a coating speed of 50 m / min to obtain a coating with a thickness of 1-5 μm. Only one side is coated to obtain a transition coating diaphragm with a thickness of 3 μm of oily positive electrode coating slurry coating. The transition coating diaphragm is then dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of Comparative Example 2.
[0134] Comparative Example 3
[0135] First, add 0.5% dispersant and 5% ethyl cellulose thickener to ethanol and stir evenly, then slowly add 10% modified PVDF powder, set the kneading machine speed to 1000rpm, and then grind and disperse the slurry through a kneading process for 60min to make the slurry mix evenly, add 10% silica aerogel and 10% poly(m-phenylenediamine) aerogel thereto, stir to make it mix evenly, the stirring time is 120min, and the speed is 1500rpm to obtain an aqueous negative electrode coating slurry.
[0136] The coating slurry is applied on a base membrane with a thickness of 5-20 μm and a porosity of 20-70% at a coating speed of 25 m / min to obtain a coating with a thickness of 1-5 μm. Only one side is coated to obtain a transitional coating diaphragm with a thickness of 3 μm of aqueous negative electrode coating slurry coating. The transitional coating diaphragm is then dried in an oven at a temperature of 30-60°C to obtain the lithium ion diaphragm of comparative example 3.
[0137] Comparative Example 4
[0138] A conventional lithium-ion separator having the same thickness as the prepared separator was used without any treatment.
[0139] The prepared lithium-ion diaphragm is tested, the oily positive electrode coating is facing the positive electrode sheet, the water-based negative electrode coating is facing the negative electrode sheet, and they are wound in sequence for hot pressing to form a lithium-ion battery cell, and then liquid is injected to form a lithium-ion battery. The positive electrode material of the positive electrode sheet is one or more of lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium manganese oxide and lithium iron phosphate, and the negative electrode sheet is graphite as the negative electrode material. Then the lithium-ion battery is tested for performance, mainly including: cycle performance test, battery liquid retention, battery internal resistance, battery capacity retention rate Battery model: 986771-5800mAh, injection volume 15.8g.
[0140] Table 1 Comparative Examples and Example Test Results
[0141]
[0142] By comparing Examples 1-4 in Table 1 with Comparative Example 4, the liquid retention capacity, battery internal resistance, and capacity retention rate after 500 cycles of the lithium battery prepared by adding aerogel additives to the lithium ion diaphragm are improved, indicating that the lithium battery prepared by adding aerogel additives to the lithium ion diaphragm has increased absorption and wetting properties of the electrolyte, and the lithium battery's ability to resist thermal shrinkage is improved.
[0143] From the comparison between Example 3 and Example 4, adding ammonium bicarbonate pore-forming agent is beneficial to reducing the internal resistance of the battery;
[0144] By comparing Example 3 with Comparative Example 1, the liquid retention capacity of the lithium battery prepared by the aerogel additive containing only inorganic aerogel is lower than the liquid retention capacity of the lithium battery prepared by the aerogel additive including inorganic aerogel and organic aerogel, indicating that the organic aerogel has a stronger ability to absorb electrolyte, thereby improving the performance of the lithium battery.
[0145] From the comparison of Example 1 and Comparative Example 2, the lithium battery made by the lithium ion diaphragm without the oily positive electrode coating has lower liquid retention, battery internal resistance, and 500-cycle capacity retention rate than the lithium battery coated with the oily positive electrode coating, and the battery full charge expansion rate increases; the lithium battery made by the lithium ion diaphragm without the water-based negative electrode coating has lower liquid retention, battery internal resistance, and 500-cycle capacity retention rate than the lithium battery coated with the water-based negative electrode coating, and the battery full charge expansion rate increases. It shows that the double-layer structure of the lithium ion diaphragm coated with the oily positive electrode coating and the water-based negative electrode coating on both sides is conducive to improving the infiltration ability of the electrolyte and improving the lithium ion exchange capacity between the lithium ion diaphragm and the positive and negative electrodes.
[0146] Comparing the positive electrode side peeling degree of the positive electrode sheet and the oily positive electrode coating of Examples 1 and 2 with the negative electrode side peeling degree of the negative electrode sheet and the water-based negative electrode coating, the bonding performance of the water-based negative electrode coating of Example 1 with the addition of 10% silica aerogel and 10% polyurea aerogel decreased, and the bonding performance of the oily positive electrode coating of Example 2 with the addition of 10% silica aerogel and 10% polyurea aerogel decreased. This indicates that the addition of aerogel additives affects the bonding performance of the oily positive electrode coating and the water-based negative electrode coating.
[0147] The above-mentioned embodiments only express several implementation methods of the present disclosure, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the disclosed patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present disclosure, and these all belong to the protection scope of the present disclosure. Therefore, the protection scope of the disclosed patent shall be subject to the attached claims.
Claims
1. A method for preparing a lithium ion separator, characterized in that: The steps include: preparing an oily positive electrode coating slurry, wherein the oily positive electrode coating slurry is added with an aerogel additive, wherein the solvent of the oily positive electrode coating slurry is butanone; preparing an aqueous negative electrode coating slurry, wherein the aqueous negative electrode coating slurry is added with an aerogel additive, wherein the solvent of the aqueous negative electrode coating slurry is ethanol; Applying the oily positive electrode coating slurry on one side of the base film and applying the aqueous negative electrode coating slurry on the other side of the base film to obtain a transition coating separator; The transition coating diaphragm is dried to remove butanone and ethanol, so as to obtain a lithium ion diaphragm in which an oily positive electrode coating, a base film and an aqueous negative electrode coating are sequentially arranged.
2. The method for preparing a lithium ion separator according to claim 1, characterized in that: The transition coating diaphragm is dried at a temperature of 30° C. to 60° C., and the baking time is 0.5 h to 3 h.
3. The method for preparing a lithium ion separator according to claim 1, characterized in that: The preparation of the oily positive electrode coating slurry comprises the following steps: Adding the positive electrode coating binder to butanone, and then adding a positive electrode coating dispersant and stirring and dispersing for 60 minutes to 120 minutes to obtain a positive electrode intermediate slurry; The aerogel additive is added to the positive electrode intermediate slurry, and the mixture is stirred and dispersed for 120 min to 150 min to obtain an oily positive electrode coating slurry; The oily positive electrode coating slurry comprises the following components by mass: Cathode coating binder: 15%-30%; Butanone: 44.5%-79.5%; Positive electrode coating dispersant: 0.5%; Aerogel additive: 5%-25%.
4. The method for preparing a lithium ion separator according to claim 3, characterized in that: The positive electrode coating binder is at least one of polyvinylidene fluoride PVDF and polyvinylidene fluoride-hexafluoropropylene copolymer PVDF-HFP; the positive electrode coating dispersant is at least one of polyethylene glycol, hexadecylbenzene sulfonic acid and modified polyacrylic acid.
5. The method for preparing a lithium ion separator according to claim 1, characterized in that: The preparation of the aqueous negative electrode coating slurry comprises the following steps: Add the negative electrode binder and thickener into ethanol, then add the negative electrode coating dispersant, and grind and disperse for 60 minutes to 120 minutes to obtain the negative electrode intermediate slurry; Adding aerogel additive to the negative electrode intermediate slurry, stirring and dispersing for 120min-150min, to obtain an aqueous negative electrode coating slurry; The aqueous negative electrode coating slurry includes the following components by mass: Negative electrode binder: 10%-20%; Thickener: 5%-10%; Ethanol: 44.5%-79.5%; Negative electrode coating dispersant: 0.5%; Aerogel additive: 5%-25%.
6. The method for preparing a lithium ion separator according to claim 5, characterized in that: The negative electrode binder is modified polyvinylidene fluoride; the negative electrode coating dispersant is at least one of polyethylene glycol, hexadecylbenzene sulfonic acid and modified polyacrylic acid.
7. The method for preparing a lithium ion separator according to claim 1, characterized in that: The aerogel additive includes organic aerogel and inorganic aerogel, wherein the inorganic aerogel is at least one of SiO2 aerogel and Al2O3 aerogel; and the organic aerogel is at least one of polyurea aerogel and polyimide aerogel.
8. The method for preparing a lithium ion separator according to claim 1, characterized in that: The thickness of the base film is 5 μm-20 μm, the thickness of the oily positive electrode coating is 1 μm-5 μm, and the thickness of the water-based negative electrode coating is 1 μm-5 μm.
9. A lithium ion separator, characterized in that: The lithium ion separator is prepared by the method for preparing the lithium ion separator according to any one of claims 1 to 8.
10. A method for preparing a lithium ion battery, characterized in that: A lithium ion membrane obtained by the method for preparing a lithium ion membrane according to any one of claims 1 to 8, Winding the positive electrode sheet, the lithium ion separator and the negative electrode sheet to form a winding core, and hot pressing the winding core to obtain a battery cell; The hot-pressed battery cell is installed in a battery housing, and then liquid is injected and formed to obtain the lithium-ion battery.
Citation Information
Patent Citations
Hydrophobic silica aerogel composite separator for lithium-ion batteries
CN106450116B
Aerogel battery diaphragm and preparation method thereof
CN114976472A
Ceramic diaphragm taking aerogel as powder body, and applications of ceramic diaphragm in lithium ion battery
CN106784558A
Water-based high-viscosity glued diaphragm, preparation method thereof, and application of diaphragm in battery
CN111129406A
Lithium-ion battery diaphragm with ultrathin coating layer
CN111180644A
Cited By
Normal-pressure drying preparation method and application of polyimide aerogel powder
CN120574430A
Normal pressure drying preparation method of polyimide aerogel powder and application thereof
CN120574430B